Pengaruh Work-Life Balance Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi Pada Pekerja Perempuan di Pabrik Bakpia Permata Agro Mandiri) - Najjah, Famirza Syifaun; Rizal, Mohammad; Paramadina, Dita Roosemella (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research was conducted to analyze the effect of work-life balance on employee performance with job satisfaction as a mediating variable. This research uses explanatory quantitative research. The data sources for this research are primary data originating from data distributing questionnaires to female workers at the Bakpia Permata Agro Mandiri Factory and secondary data originating from journals, previous researchers and other sources. The population and sample of this research is 36, namely all female employees at the Bakpia Permata Agro Mandiri Factory using a probability sampling technique. The data analysis technique in this research uses SEM-PLS. The results of this research show that in a direct relationship work-life balance has a positive and significant effect on employee performance, work-life balance has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and work-life balance has a positive and significant effect on employee performance mediated by the job satisfaction variable for female workers at the Bakpia Permata Agro Mandiri Factory. Keywords: Work-Life Balance, Employee Performance, and Job Satisfaction